2009
DOI: 10.1161/circulationaha.109.852517
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Delayed-Enhancement Magnetic Resonance Imaging

Abstract: Background-Left ventricular ejection fraction is a powerful independent predictor of survival in cardiac patients, especially those with coronary artery disease. Delayed-enhancement magnetic resonance imaging (DE-MRI) can accurately identify irreversible myocardial injury with high spatial and contrast resolution. To date, relatively limited data are available on the prognostic value of DE-MRI, so we sought to determine whether DE-MRI findings independently predict survival. Methods and Results-The medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(90 citation statements)
references
References 35 publications
10
77
0
Order By: Relevance
“…Yet, the low prevalence of LGE reported in our work is concordant with the observed improvement in systolic function shown by echocardiographic results from the parent study 1. Since LGE indicates irreversible focal myocardial damage, even when ejection fraction is preserved,8, 9, 10 the overall low prevalence of LGE in this study represents an optimistic finding. Indeed, the CMR literature consistently indicates that LGE is associated with persistent myocardial dysfunction despite medical therapy,11, 12 arrhythmia,4, 13, 14 and in turn, adverse clinical events such as hospitalization for heart failure, arrhythmia, and mortality 4, 8, 10, 14, 15.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Yet, the low prevalence of LGE reported in our work is concordant with the observed improvement in systolic function shown by echocardiographic results from the parent study 1. Since LGE indicates irreversible focal myocardial damage, even when ejection fraction is preserved,8, 9, 10 the overall low prevalence of LGE in this study represents an optimistic finding. Indeed, the CMR literature consistently indicates that LGE is associated with persistent myocardial dysfunction despite medical therapy,11, 12 arrhythmia,4, 13, 14 and in turn, adverse clinical events such as hospitalization for heart failure, arrhythmia, and mortality 4, 8, 10, 14, 15.…”
Section: Discussionsupporting
confidence: 89%
“…While LGE can occur even when ejection fraction is preserved,8, 9, 10 LGE is generally associated with persistent myocardial dysfunction despite medical therapy,11, 12 arrhythmia,4, 13, 14 and in turn, hospitalization for heart failure, arrhythmia, and mortality 4, 8, 10, 14, 15. Regardless of etiology, LGE is prognostically adverse across the spectrum of left ventricular ejection fraction (LVEF), even when preserved 4, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of myocardial fibrosis is associated with ventricular functional recovery in patients with NICM with high sensitivity (90.5%), specificity (79.2%), positive predictive value (80.0%) and negative predictive value (90.9%) (49). In a survival analysis, cardiac fibrosis was found to be the most important independent predictor of mortality/transplantation requirement, especially in patients with LVEF < 30% who already had increased mortality, survival was found to be decreased in the presence of delayed enhancement (50). Wu et al (21) demonstrated that in NICM with late gadolinium enhancement on CMR, probability to experience adverse cardiac outcomes such as HF hospitalization, implantable cardioverter-defibrillator (ICD) discharge, and cardiac death increased eight fold after adjustment for LV volume index and functional class.…”
Section: Cardiac Fibrosis and Prognosismentioning
confidence: 97%
“…51,[126][127][128][129] Gerber et al 46 recently reported on 144 patients with mean EF 24% and ischemic cardiomyopathy, who underwent DCE CMR followed for three years. Seventy nine patients underwent CABG, 7 had PCI, and 58 patients received medical therapy alone.…”
Section: Outcomes Studies In Patients With Cmr and Lgementioning
confidence: 99%